Meaningful community engagement in public-private partnerships: a case study of Manhattan’s downtown redevelopment project - Khaleghi Kerahroodi, Mehraz (Kansas State University, 2016)
Public-private partnerships (PPPs) have become a vehicle to deliver products and services internationally. It is a favored strategy widely adopted for implementing complex urban developments in the United States. However, the complex nature of such partnerships raises serious concerns about meaningful community engagement. Meaningful community engagement is a result of the presence and quality of transparency and public participation elements that are strongly correlated. The following research describes how the community was involved and contributed to an urban development PPP project in Manhattan, Kansas. The research goal is to understand the mechanism of the community engagement in a PPP project and to evaluate the quality of the process at the local level from a planning perspective. With an in-depth case study and an understanding of meaningful community engagement processes, this research will contribute to the body of knowledge in the area of PPPs and meaningful community engagement at the local level and evaluate local PPP policies and practices. The first objective is to evaluate the participation opportunities with a developed Community Engagement Attribute Evaluation System (CEAES) based on the recognized metrics of quality practices. Attributes are drawn from the identified characteristics of quality transparency and quality public participation of meaningful practices. The second goal is to interview the key stakeholders of the project from the public sector, the private sector, and the community and add depth to the findings that complements the overall evaluation. Through both technical evaluation and open-ended personal interview, this study attempts to describe the design and the process of public participation practices. Analysis will show whether or not the community was meaningfully engaged and if the technical aspects of a quality community engagement practice were present. Finally, this study aims to inform future similar planning practices. The result serves two local purposes of planning governance and policy. For the former, it will help those with no record of PPP to better design and implement the engagement process; and for the ones with PPPs’ experience, it will contribute to the quality of the future partnerships. For the latter, it will guide the local governments and policy makers to better address PPPs’ ongoing issue of community engagement.
Keywords: Public-Private Partnerships; Meaningful community engagement; Urban re/development; Transparency; Public Participation; Public Administration (0617); Urban Planning (0999)